Spoehr, Alexander: Marianas prehistory, archaelogical survey and excavations on Saipan, Tinian and Rota. Fieldiana: Anthropology, Vol. 48. Chicago Natural History Museum. 187 pp. Chicago, 1957. - Schobinger, Juan (1957)
Fil: Schobinger, Juan. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras